Non-surgical methods of pain treatment improving the quality of life of patients with endometriosis - Golemo, Jagna; Gryc, Anna; Nowińska, Aleksandra; Grudzień, Monika; Świdziński, Rafał (Journal of Education, Health and Sport, 2022)
Introduction : Endometriosis is a disease that currently affects 10-15% of women of reproductive age worldwide. The main problem of female patients, in addition to infertility, is pain, which varies greatly, significantly reduces the quality of life and affects family, social, sexual and professional life. Pharmacological treatment, which is applied both after the excision of the lesions and in patients who were not eligible for surgery, is an important element of pain therapy. There are also other methods, such as appropriate diet change, supplementation, acupuncture, electrotherapy, which are partially effective. Method : review of the recent literature based on PubMEd ,Google scholar research based on the following keywords : endometriosis treatment, hormonal treatment of endometriosis, quality of life of patients with endometriosis Purpose of work : Comparison of the mode of action and effectiveness of individual non-surgical methods of treating pain in patients with endometriosis.